Formation of initial changes in hemodynamics and fluid compartments in high surgical risk patients under the influence of acute abdominal pathology - O.V. Kravets; V.V. Yekhalov; D.A. Krishtafor; O.O. Zozulia; O.O. Volkov; O.O. Vlasov (Medičnì Perspektivi, 2021)
Among the main factors of pathological changes that accompany acute abdominal pathology are the inflammatory process of the peritoneum and fluid deficiency due to its pathological losses. The aim of our study was to analyze the initial state of fluid compartments of the body and hemodynamics in high surgical risk patients with acute surgical abdominal pathology. There were examined 157 patients with acute abdominal pathology who underwent emergency laparotomy. The presence and severity of fluid deficiency were determined clinically by tissue hydrophilicity test by P.I. Shelestiuk, biochemically – by assessing the levels of hematocrit, hemoglobin, erythrocytes, blood electrolytes, vasopressin (ADH) and brain natriuretic propeptide (proBNP), as well as the mean erythrocyte volume and plasma osmolarity. Variables of fluid compartments of the body and central hemodynamics were studied using the non-invasive bioimpedancemetry. Based on the values of oxygen concentration in arterial and venous blood, total oxygen consumption (VO2) and delivery of oxygen (DO2), oxygen extraction ratio (O2ER) were calculated. The detected changes indicate intravascular fluid deficiency and concomitant hemoconcentration with normal electrolytes levels and plasma osmolarity. In patients with high surgical risk and moderate dehydration according to P.I. Shelestiuk, urgent surgical pathology of the abdominal cavity reduces extracellular fluid volume by 19.1% (p=0.019) of the reference by reducing the volume of the interstitium and intravascular fluid respectively by 20.7% (p=0.002) and 16.3% (p=0.001) of regional values, which forms in patients a state of "volume depletion" of moderate severity. This is accompanied by an increase in the ADH concentration by 16.7% (p=0.041) above reference and normal proBNP levels. Stroke volume decreases by 28.8% (p=0.021) against tachycardia (increase in heart rate by 39.7% (p=0.001) above normal) and vascular spasm (increase in systemic vascular resistance by 86.9% (p=0.001) above reference), which supports the normodynamic type of blood circulation (cardiac index – 3.2 (0.4) l/min/m2) with the decrease in stroke index and peripheral perfusion index by 41.3% (p=0.002) and 55.2% (p=0.002) from reference, respectively. DO2 decreases by 11.1% (p=0.011) from reference with VO2 increased by 16.3% (p=0.004) above reference, which leads to a decrease in oxygen utilization by 7.2% (p=0.041) from reference.